Manifest ethical-aesthetic-political-affirmative experimental-libertarian for a experimentation research - Stubs, Roberta (Revista Hipótese, 2016)
This manifest is an invitation to think and research by overflow, to create spaces of experimentation and practices involving the seizure of affection, desires and flows that says about the exuberance of life. It is a search for the expansion of our horizons of experience, as well as a fight for the exponential increase in our practices of freedom, which can not be restricted to categories and identities.
Keywords: Post identitarian figurations; Body-experience; Production of subjectivity; Art; Becoming; Feminisms